Laparoscopic spleen-preserving distal pancreatectomy with splenic vessel preservation for pancreatic pseudocyst in a 10-year-old boy - Ali İhsan Anadolulu; Mehmet Tolga Kafadar; Mehmet Ali Gök; Zeynep Anadolulu (Elsevier, 2018)
Regarding the practice of pediatric surgery, treatment methods in cystic masses of the pancreas are still controversial. Nowadays, open surgery methods are becoming less popular thanks to the common use of laparoscopic surgery. Spleen preserving surgery is also emphasized, especially for the prevention of splenectomy-related complications in distal pancreas surgery. However, there is not sufficient study for the pediatric age group. In this article, a 10 year old male patient who has consulted for medical advice on abdominal pain and had a history of abdominal trauma of 8 months ago is presented. 7 × 6 cm cystic mass in the distal part of the pancreas was reported with the help of radiological imaging upon the physical examination that remarked abdominal distention. The patient received laparoscopic distal pancreatectomy with splenic preservation. As a result of histopathological examination, it was interpreted as pancreas pseudocyst. We consider that laparoscopic spleen preserving surgery can be operated safely with regards to the distal pancreatic masses in children both for the purpose of short span of time spend in the postoperative hospital stay and the prevention of complications due to infection and splenectomy.